1996
DOI: 10.1084/jem.184.6.2423
|View full text |Cite
|
Sign up to set email alerts
|

The V–J Recombination of  T Cell Receptor-γ Genes Is Blocked in Interleukin-7 Receptor–deficient Mice

Abstract: IL-7R-deficient mice have severely impaired expansion of early lymphocytes and lack γδ T cells. To elucidate the role of IL-7R on γδ T cell development, we analyzed the rearrangements of TCR-α, β, γ, and δ genes in the thymus of the IL-7R-deficient mice. Southern blot analysis with a Jγ1 probe revealed that more than 70% of Jγ1 and Jγ2 alleles are recombined to form distinct Vγ1.2–Jγ2 and Vγ2–Jγ1 fragments in control mice. On the contrary, no such recombination was detected in the mutant mice. The rearrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 35 publications
7
82
0
Order By: Relevance
“…Furthermore, IL-7 participates in regulation of the maintenance and the strength of the immune response and regulates the development and the cytolytic activity of intestinal ␥␦ intraepithelial lymphocytes (36,40,41). These intraepithelial lymphocytes represent the frontline defense alimentary and bacterial gut lumen Ags and depend on IL-7R␣ signaling (42). Thus, IL-7R␣ signals IL-7-mediated critical specific actions on T cell development and function, yet the control of its expression remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-7 participates in regulation of the maintenance and the strength of the immune response and regulates the development and the cytolytic activity of intestinal ␥␦ intraepithelial lymphocytes (36,40,41). These intraepithelial lymphocytes represent the frontline defense alimentary and bacterial gut lumen Ags and depend on IL-7R␣ signaling (42). Thus, IL-7R␣ signals IL-7-mediated critical specific actions on T cell development and function, yet the control of its expression remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Crompton et al found that the introduction of a transgenic TCR in IL-7 receptor ␣-deficient animals reconstituted thymocyte development, suggesting that the failure to undergo TCR ␣␤ gene rearrangements is one cause of the developmental block in the absence of IL-7R signaling [43]. In addition, IL-7 has been shown to be required for V-J recombination of TCR ␥ chain genes [44]. This latter finding provides an explanation for the complete absence of ␥␦ T cells in IL-7-, Jak3-, and ␥c-deficient mice.…”
Section: Early T Cell Maturation In the Thymus Of Adult Jak3-deficienmentioning
confidence: 99%
“…However, because IL-7Ra-mediated signaling is indispensable for expression of the functional g-chain, gd T cells are completely absent in IL-7Ra 2/2 mice (Fig. 4A) (36,37). To circumvent this effect, we used the previously established system that gd T cell development in IL-7Ra 2/2 mice was rescued by introduction of a rearranged g-chain (38).…”
Section: Il-7ra-mediated Signaling Is Required For Homeostasis Of Il-mentioning
confidence: 99%